Antitumour Activity of a Hinge- and Fc-engineered Chimeric Heavy-chain Antibody - D'Eall, Calvin (Université d'Ottawa / University of Ottawa, 2015)
EG2-hFc is an ≈ 80 kDa chimeric heavy-chain antibody comprised of human IgG1 hinge and fragment crystallisable bivalently linked to EG2; a camelid-derived, heavy chain antibody variable domain specific for the human epithelial growth factor receptor 1 and its associated EGFRvIII mutant. Though previous work revealed EG2-hFc to demonstrate impressive in-vivo tumour accumulation, it’s therapeutic potential, as well as that of chimeric heavy-chain antibodies in general, remains largely unexplored. With this in mind, our current study was successful in showing that EG2-hFc could facilitate in-vitro antibody-dependent cell-mediated cytotoxicity of epithelial growth factor receptor-positive breast cancer cells. Additionally, EG2-hFc’s intrinsic cytotoxicity was augmented following the implementation of engineering strategies that are currently being explored in the context of conventional anti-cancer monoclonal antibodies: including the modification of a conserved N-linked CH2 glycan, as well as the alteration of EG2-hFc’s hinge length. Collectively, these findings contribute to the growing body of research that has revealed chimeric heavy-chain antibodies to be a promising class of novel anti-tumour therapeutics.
Keywords: Antibody; ADCC